2015
DOI: 10.1007/s13762-015-0807-0
|View full text |Cite
|
Sign up to set email alerts
|

Soil microbial functionality in response to dairy sewage sludge and mineral fertilisers application under winter rape

Abstract: Microbial activity and the diversity of their catabolic potential would be stratified according to soil profile as a result of differing content of soil organic C and they would be altered by applying dairy sewage sludge (DSS) to the surface and subsequently ploughing. We applied 26 Mg ha -1 of DSS and the same nutrient dose of mineral fertilisers as an NPK reference to the soil before sowing winter rape (Brassica napus) in the field experiment. We evaluated the impact of the fertilisers on microbial activity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…This is supported by the positive correlations between all the analysed enzymatic parameters and the C org content and between almost all parameters and the total N content (Table 10). Similar correlations, although in different experimental conditions, were reported by other authors (Oszust et al 2015;Taylor et al 2002). It should be emphasised, however, that the studies cited here were conducted in different experimental conditions, i.e.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…This is supported by the positive correlations between all the analysed enzymatic parameters and the C org content and between almost all parameters and the total N content (Table 10). Similar correlations, although in different experimental conditions, were reported by other authors (Oszust et al 2015;Taylor et al 2002). It should be emphasised, however, that the studies cited here were conducted in different experimental conditions, i.e.…”
Section: Resultssupporting
confidence: 88%
“…Furthermore, strong correlations of the above-mentioned enzymatic activities with microbial abundance and organic matter content were found. Many studies have evidenced the suitability of enzymatic tests for evaluation of the effects of application of sewage sludge into soils (Franco-Otero et al 2012;Joniec et al 2015;Oszust et al 2015). The study results demonstrated a generally positive effect of waste on the enzymatic activity in soil.…”
Section: Introductionmentioning
confidence: 87%
“…Islam et al (2011) used CLPP and the activity of β-glucosidase for evaluating the condition of soils fertilised with mineral fertilisers and compost. Some authors have demonstrated the effectiveness of the CLPP method in assessing the impact of sewage sludge on the soil environment (Oszust et al, 2015;Ros et al, 2006a;Suhadolc et al, 2010). Enzymatic activity is widely employed in monitoring ecological soil conditions, including degraded soils.…”
Section: Introductionmentioning
confidence: 99%
“…Natural utilisation of sewage sludge is proper from the ecological point of view and has a favourable effect on the reclamation of degraded soils. This approach of sludge utilisation affects positively the plant yields and reduces the use of mineral fertilisers-so it would be much more beneficial for the environment (Hussein et al 2010;Jezierska-Tys et al 2010;Oszust et al 2015). An important factor that makes dairy sewage sludge applicable in agriculture is the fact that it abounds in such elements as nitrogen, magnesium, calcium and phosphorus.…”
Section: Introductionmentioning
confidence: 99%